Compliance minimization of thin plates made of material with predefined Kelvin moduli. Part I. Solving the local optimization problem (Archives of Mechanics - Test, 2012)
The paper deals with compliance minimization of a transversely homogeneous plate, subjected to the in-plane and transverse loadings acting simultaneously. The set of design variables includes the eigenstates of Hooke’s tensor whose eigenvalues, i.e. Kelvin moduli fields, are assumed to be fixed on the middle plane of the plate, but no isoperimetric condition is imposed. The optimization task reduces to an equilibrium problem of an effective hyperelastic plate. The effective potential is explicitly expressed in terms of the invariants of both the strain fieldsinvolved.